Electrophoretic Banding Patterns of Esterase Isozymes of Fresh Water Fish [Channa punctatus (Bloch)] - Venkateswara Rao Mandalapu; Venkaiah Yanamala (Innovations in Biological Science Vol. 5, 2024)
Pesticides find a potential application in agriculture, combating pest and enhancing productivity. But on the reared, pesticides find their way into aquatic habitats such as rivers, lakes and ponds, thereby affecting aquatic flora and fauna. These pesticides cause significant variation in esterase Isozyme patterns particularly in fish. The present investigation was focused on the electrophoretic banding patterns of esterase Isozyme in gill, liver, and brain tissues of the freshwater fish Channa punctatus (Bloch) at different time intervals i.e. 24H, 48H, 72 H and 96 hrs after exposure of Malathion to those compared with control group, the quantitative analysis of the esterase Isozymes were performed by using 7.5 % of native polyacrylamide gel electrophoresis (PAGE) and stained with \(α\)-naphthyl acetate as substrate. The relative motilities (Rm) of three esterase isozyme bands in gill, liver, brain tissue were observed to be 0.60±0.05, 0.4±0.5. and 0.30±0.05 and bands were designated as Est-1, Est-2, and Est-3, respectively. Compared to control group, both Est 2 and Est-3 esterase isozyme bands in gill and liver tissue were eliminated on exposure to Malathion, at 72 H and 96 hrs.